OPTIMALISASI PERLINDUNGAN HUKUM TENAGA KERJA DALAM ASPEK KESELAMATAN KERJA PADA PROYEK KONSTRUKSI DI WILAYAH BOGOR - dani purwanto; Ujang Bahar; endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2020)
Lack of awareness of workers is one of the factors causing work accidents that have occurred. This cannot be done as it should, so there are still frequent work accidents involving construction project workers. In the Bogor region itself, the issue of work safety is also a special concern of the government in realizing development. The method used by the author in this study is a descriptive legal normative research method, the implementation of work safety protection for construction project workers in Bogor City is still not running optimally, this is due to the absence of an agreement between workers and employers. Because in general construction project workers only have a working relationship with third parties outside the construction company. So that the participation of the government is needed to resolve work safety issues for construction project workers. The legal consequence arising from the absence of a work agreement for construction project workers is that they do not receive work health and safety insurance, other than that the wages received do not correspond to what has been provided by the company, because there is a third party tasked with coordinating these workers, so construction project workers do not have legal protection as mandated by law.